STUDI PUSTAKA IMPLEMENTASI KURIKULUM MERDEKA DAN TANTANGAN PENDIDIKAN ANAK SEKOLAH DASAR - Salsa Bella, Ainun; Jariah, Siti Ainun; Siti Fatimah; Almadani, M. Seman; Ahmad Suriansyah; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the Merdeka Curriculum in elementary schools marks a new direction in education that is more flexible, student-centered, and focused on meaningful learning. However, its implementation still faces various challenges, particularly related to teacher readiness, disparities in students’ learning abilities, and suboptimal parental involvement. This study aims to identify the main obstacles in implementing the Merdeka Curriculum and examine their impact on the quality of learning in primary education. Using a literature review method, this research analyzes scientific articles, policy documents, and recent studies published within the last five years. The findings indicate that although the Merdeka Curriculum promotes deep learning, differentiation, character development, and 21st-century skills, its effectiveness is hindered by teachers who feel overwhelmed in adapting their instructional strategies, students’ generally low academic performance, high absenteeism rates, and the policy all students to grade up, which also affects assessment dynamics. In addition, limited infrastructure, unequal access to technology,  and weak collaboration among schools, families, and communities further exacerbate the challenges of implementation. This study concludes that systemic support, continuous professional development, and strengthened partnerships among schools, families, and communities are key to realizing an effective, sustainable, and goal-aligned implementation of the Merdeka Curriculum in primary education.